2016
DOI: 10.1097/opx.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Vision Impairment and Ocular Morbidity in a Refugee Population in Malawi

Abstract: The prevalence and causes of blindness and vision impairment in a refugee population are comparable with those of the general population. Lack of basic eye care services in the health center for refugees is a major concern. The health care facility in the settlement camp needs to be upgraded to provide comprehensive eye care including refractive care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Holden and colleagues (Holden et al, 2008) identified two different presbyopia definitions in epidemiological studies of presbyopia: 1) functional presbyopia, defined as needing a significant optical correction added to the presenting distance refractive correction to achieve a near visual acuity absolute (such as N8 or J1) or relative (such as 1 line of acuity M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT improvement) criteria; or 2) objective presbyopia, where the significant optical correction is defined (such as ≥1.00 D) and added to the best optical distance correction to achieve a defined near visual acuity. In more recent epidemiological studies, however, presbyopia is typically defined as a person aged greater or equal to 35 years who is unable to read binocularly N8 (or 6/12) at 40 cm or their habitual working distance, and additionally in some studies limited to those whose near vision improves with additional lenses (Cheng et al, 2016;Girum et al, 2017;Kaphle et al, 2016;Muhit et al, 2018;Nsubuga et al, 2016).…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Holden and colleagues (Holden et al, 2008) identified two different presbyopia definitions in epidemiological studies of presbyopia: 1) functional presbyopia, defined as needing a significant optical correction added to the presenting distance refractive correction to achieve a near visual acuity absolute (such as N8 or J1) or relative (such as 1 line of acuity M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT improvement) criteria; or 2) objective presbyopia, where the significant optical correction is defined (such as ≥1.00 D) and added to the best optical distance correction to achieve a defined near visual acuity. In more recent epidemiological studies, however, presbyopia is typically defined as a person aged greater or equal to 35 years who is unable to read binocularly N8 (or 6/12) at 40 cm or their habitual working distance, and additionally in some studies limited to those whose near vision improves with additional lenses (Cheng et al, 2016;Girum et al, 2017;Kaphle et al, 2016;Muhit et al, 2018;Nsubuga et al, 2016).…”
Section: 1mentioning
confidence: 99%
“…As highlighted previously, presbyopia has been estimated to affect 1.37 billion people worldwide by the year 2020 (Holden et al 2008). While the impact of presbyopia can be minimised relatively easily by use of a visual correction, such as spectacles, contact lenses or refractive surgery (see section 5), these corrections have a financial burden (Naidoo et al, 2016) and it is estimated that globally over 50% of adults >50 years (up to over 50% of developing world where there is a lack of awareness and accessibility to affordable treatment options (Cheng et al, 2016;Girum et al, 2017;Hookway et al, 2016;Muhit et al, 2018;Schellini et al, 2016) and up to 34% even in developed countries) do not have adequate near correction, impacting task performance and productivity (Frick et al, 2015;Holden et al, 2008;Kaphle et al, 2016;Man et al, 2016;Nsubuga et al, 2016;Zebardast et al, 2017). Even in developed countries, increasing digital demands are associated with asthenopia, perhaps due to latent accommodative dysfunction, in people in their thirties, which is a form of largely undiagnosed early onset presbyopia (Reindel et al, 2018).…”
Section: Presbyopia Social and Economic Impactmentioning
confidence: 99%
“…myopia generally reported in economically deprived settings [20] and may also indicate a higher prevalence of other, nonrefractive ocular conditions such as infections [21,22], which have been documented in the Rohingya camps. The existing literature on visual health among displaced populations, including a recent review [11], has documented high prevalence of blindness [12,[22][23][24][25] in these communities, ranging from 1.3% to 26.2% [11]. However, few published studies [26][27][28][29] have focused on the delivery of eye care services rather than simply assessing the existing burden, and none of these have measured the demand for comprehensive eye care service in a defined refugee community, beyond a single disease focus such as refractive error [27][28] or trachoma [29].…”
Section: Plos Medicinementioning
confidence: 99%
“…However, these initiatives have largely focused on the needs of settled populations. A growing body of information exists about the visual health and unique eye care needs of displaced people [11,12], and there is increasing awareness of the unmet need for vision care in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…14 Further, a 2016 Malawian study also reported similar causes of vision impairment in their cohort of refugees and emphasised the importance of comprehensive eye-care services, particularly optometric, for refugees in settlement camps. 15 Studies on refugee eye health are also important because they can influence both the strategic planning and local delivery of eye-care practice which can then translate into better service provision and resource utilisation. For example, successful training of refugee health workers in basic optics have led to efficient screening services for uncorrected refractive error and the on-site provision of glasses across refugee camps located in the Thailand-Burma border.…”
mentioning
confidence: 99%